Social prerequisites of modernization assessment of physical fitness of primary school students - Пелешенко [Igor Peleshenko], Ігор Миколайович (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]-->The results of the survey conducted among 1,372 parents of primary school pupils of secondary schools of Kharkiv region. Found that about half of the pupils’ parents are unhappy with the system evaluation of physical fitness of their children. Parents believe that the testing system should include some exercises that determine the development of every physical quality. In particular, the test system should be accessible to children with poor health. Also, the respondents expressed the desire for the introduction into the curriculum of a special module on technical and physical preparation of students for the test.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->